Evaluation of a social marketing intervention promoting oral rehydration salts in Burundi - Nzohabonayo Jerome; Kays Megan B; Kassegne Sethson (BMC, 2011)
Abstract Background Diarrhea is the second leading cause of death for children under five in Burundi; however, use of oral rehydration salts (ORS), the recommended first-line treatment, remains low. In 2004, PSI/Burundi launched a social marketing intervention to promote ORASEL among caregivers of children under five; the product was relaunched in 2006 with a new flavor. This study evaluates the intervention after the ORASEL relaunch, which included mass media and interpersonal communication activities. The study looks at trends in ORASEL use in Burundi and in behavioral determinants that may be related to its use. Methods In 2006 and 2007, PSI conducted household surveys among Burundian females of reproductive age (15-49). Both surveys used a two-stage sampling process to select 30 households in each of 115 rural and urban collines throughout the nation. Survey respondents were asked about diarrhea treatment-related behavior; key behavioral determinants; and exposure to the ORASEL intervention. Data were analyzed to identify trends over time, characteristics of ORASEL users, and associations between exposure to the intervention and changes in ORASEL use and related behavioral determinants. Results ORASEL use among caregivers at their children's last diarrheal episode increased significantly from 20% in 2006 to 30% in 2007, and there were also desirable changes in several behavioral determinants associated with ORASEL use. Evaluation analysis showed that a higher level of exposure to the social marketing campaign was associated with greater use of ORASEL and with significant improvements in perceived availability, knowledge of the signs of diarrhea and dehydration, social support, and self-efficacy. Conclusions ORS use can be improved through social marketing and educational campaigns that make the public aware of the availability of the product, encourage dialogue about its use, and increase skills and confidence relating to correct product preparation and administration. Further interventions in Burundi and elsewhere should promote ORS through a variety of mass media and interpersonal communication channels, and should be rigorously evaluated in the context of the total market for diarrhea treatment products.